Clinical and Morphological Observation of a Child with Congenital Pneumocystis Infection - E. R. Samitova; M. S. Savenkova; T. N. Ermak; I. E. Koltunov; A. N. Kislyakov; A. G. Talalaev; L. V. Leonova; M. P. Shalatonin; N. B. Karazhas; T. N. Rybalkina; M. Yu. Kornienko (Детские инфекции (Москва))
The article presents an interesting case of congenital infection pneumocystis conclusively proven and confirmed by various methods of laboratory diagnostics, including morphological with a special color. In addition, parents were surveyed, which were the source of infection. Congenital pneumonia, especially in preterm infants, are a direct threat to life. In this regard, the timely examination of the mother and child, as well as the appointment of etiotropic antibacterial drugs is an important task to prevent the fatal outcome of the disease.